If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12y = 77 Solving 6x + 12y = 77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 6x + 12y + -12y = 77 + -12y Combine like terms: 12y + -12y = 0 6x + 0 = 77 + -12y 6x = 77 + -12y Divide each side by '6'. x = 12.83333333 + -2y Simplifying x = 12.83333333 + -2y
| -1.5x+-14.5=-31 | | -2(y-4)=20+2y-12 | | 24.6=29+a(14.51) | | (7/2+2*2)*10= | | 0.7n=-3.5 | | -8(n-5)=2(4n+11) | | 2000+0.05=3600 | | 7x+9+4(x+4)+2= | | 14(t+9)=84 | | -3x-17=-8 | | (x-110)+(3x-10)+(2x)=180 | | 8(7+6b)= | | 2x-125=400 | | 26-2x=2x+3 | | 4(y+7)=5(y-8) | | 46.5=5.25+15 | | 14ab=c | | -89-17= | | (110-x)+(3x-10)+(2x)=180 | | -9x+4=-6+-17 | | 45y^2+10y=0 | | -3-3(1-7x)=4x-40 | | ln(7x)=ln(40-x) | | -5(5W+1)=25 | | w-(-7)=51 | | 80-4x=100-y | | 10+24n=130 | | 6+3z-3=7z+12-3z | | x-(3x+4)=10 | | -3.4x+2=-3.72 | | (?2-1)=?2+1 | | 5/14+2/7= |